Rituals and social capital in the book of Leviticus? An attempt at an interdisciplinary discussion - Meyer, Esias E (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The article is an attempt by an Old Testament scholar to engage with a debate taking place in practical theology. This debate is about the influence of religion and ritual on the formation of social capital. The author attempts to shed light on this debate by looking at the two halves of the book of Leviticus, the first half of which is dominated by ritual and the second half is characterised by a broader communal perspective.